Oilseed Cover Crops for Sustainable Aviation Fuels Production and Reduction in Greenhouse Gas Emissions Through Land Use Savings - Taheripour, Farzad; Sajedinia, Ehsanreza; Karami, Omid (Frontiers in Energy Research, 2022)
Induced Land Use Changes (ILUCs) can decrease the environmental benefits of Sustainable Aviation Fuels (SAFs) if produced from traditional food crops. The development of oilseed cover crops can eliminate the side effect of ILUCs for biofuel production because they come in rotation with the major crops with some savings in demand for new cropland. This study implemented Life Cycle Analysis (LCA) and GTAP-BIO to estimate ILUC emissions values, the potentially available area, and total possible emissions savings of producing SAFs from carinata, camelina, and pennycress in the United States. The results suggest that: 1) the meals produced in conjunction with increases in Sustainable Aviation Fuel production from carinata, camelina, and pennycress could reduce land use emissions by 12.9, 15.3, and 18.3 gCO2e/MJ, respectively; 2) the total area of available land for producing these feedstocks could be about 29.3 million ha in 2035; and 3) using this area of land for SAF production, depends on the mix of oilseed cover crops that can be produced in practice, could generate up to 92 million metric tons of savings in GHG emissions per year. The projected emissions savings is about 11% of the current global GHG emissions generated by the aviation industry. Providing incentives to encourage farmers to produce these cover crops and facilitating investment in producing SAF from these cover crops are the most important factors that could help the aviation industry to enhance emissions savings.